Cooperation in international environmental negotiations due to a preference for equity - Andreas Lange; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper demonstrates that cooperation in international environmental negotiations can be explained by preferences for equity. Within a N-country prisoner?s dilemma in which agents can either cooperate or defect, in addition to the standard non-cooperative equilibrium, cooperation of a large fraction or even of all countries can establish a Nash equilibrium. In an emission game, however, where countries can choose their abatement level continuously, equity preferences cannot improve upon the standard inefficient Nash-equilibrium. Finally, in a two stage game on coalition formation, the presence of equity-interested countries increases the coalition size and leads to efficiency gains. Here, even a stable agreement with full cooperation can be reached.
Keywords: H41; D63; C7; Q00; 330; international environmental negotiations; cooperation; equity preference; coalition formation; Internationale Umweltpolitik; Verhandlungstheorie; Kooperatives Spiel; Gerechtigkeit; Theorie